Community diversity and the other-race effect in infancy - Bauer, Trinity; Hall, Cidnee; Bursalıoğlu, Aslı; Guy, Maggie W. (Frontiers in Psychology, 2023)
The other-race effect (ORE) is characterized by processing advantages for faces of one's own race over faces of another race and is observed by approximately 9 months of age. Environmental exposure to other races has an impact on the development of the ORE. In the current study, we examined the effects of community racial diversity on the ORE in 9-to 12-month-olds from across the United States. We hypothesized that community racial diversity would influence the amount of experience that infants have with individuals of other races and be an important factor in predicting the ORE across broad regions of the U.S. We predicted that infants from more diverse communities would demonstrate successful processing of own-and other-race faces, while infants from less diverse communities would demonstrate successful processing own-race, but not other-race faces. This would indicate that the ORE is exhibited more strongly in infants from less diverse communities than infants from more diverse communities. Participants completed familiarization and visual paired comparison trials with own-and other-race faces in an online study. Our results showed that although the ORE was present, the effect was driven by community racial majority members. Recognition biases were not observed in community racial or ethnic minority participants, potentially due to increased exposure to racial outgroup members mitigating the development of the ORE in this subset of participants. This study has far-reaching implications in the study of infant face perception, child development, and social justice, as the ORE develops at a young age, and may lead to a complex pattern of racial biases contributing to systemic barriers in society.